Dear Santa a novel - Macomber, Debbie (New York : Ballantine Books, 2021)
"Lindy Carmichael isn't feeling particularly joyful when she returns home to Wenatchee, Washington, for Christmas. The man she thought was the one has cheated on her with her best friend, and she feels completely devoid of creativity in her graphic-design job. Not even carolers or Christmas cookies can cheer her up but Lindy s mother, Ellen, remembers an old tradition that might lift her daughter's spirits. Reading through a box of childhood letters to Santa and reminiscing about what she'd wished for as a young girl may be just the inspiration Lindy needs. With Ellen's encouragement, she decides to write a new letter to Santa, one that will encourage her to have faith and believe just as she d done all those years ago. Little does Lindy know that this exercise in gratitude will cause her wishes to unfold before her in miraculous ways."
Includes a preview from the author's Jingle all the way (pages 241-259).
109331
Keywords: Santa Claus -- (Fictitious character); Mothers and daughters; Man-woman relationships; Letters; Letter writing; Christmas; Washington (State); Christmas stories; Romance fiction